ARTIKEL DITARIK: [Pengaruh Konseling Farmasis Terhadap Pengetahuan dan Kepatuhan Pasien HIV/AIDS di Poliklinik VCT RSUP Dr. M. Djamil Padang] - Jelly Permatasari; Dedy Almasdy; Raveinal Raveinal (Fakultas Farmasi Universitas Andalas, 2017)
Adherence to antiretroviral therapy is key to sustained HIV suppression, reduced risk of drug resistance, improved quality of life, and survival of HIV/AIDS patients. A pharmacist is in charge in optimizing the result of the therapy by providing counseling to increase the patients’ knowledge which finally increases the quality of life. The objective of this study was to explore the impact of pharmacist counseling toward knowledge and adherence of patients with HIV/AIDS. The study was conducted in quasi-experiment with a design of one group pretest-posttest. The setting of this study was conducted in VCT RSUP DR. M. Djamil Padang. Data were collected through questionnaires and medical records. Patients’ knowledge and adherence were scored by using knowledge aspect questionnaire and MMAS-8 questionnaire. All questionnaires had been tested for validity and reliability. The data were analyzed by Wilcoxon test and paired t-test. A number of 124 patients completed all follow-ups of study. The result of this study showed that there was a significant increase of patients’ knowledge (p=0,00) and adherence (p=0,00) after the counseling. The study concluded that pharmacist counseling could increase patients’ knowledge and adherence to the therapy.